Health System in Nigeria : From Underperformance to Measured Optimism - Adeyi, Olusoji (Taylor and Francis, 2016)
The past five decades have seen numerous health policies and development plans in Nigeria, culminating in the National Health Act of 2014.8 The Act provides for a range of responsibilities, instruments, and institutions, covering but not limited to: responsibility for health, eligibility for health services, and establishment of a national health system; financing; health establishments and technologies; rights and obligations of patients and healthcare personnel; national health research and information system; human resources for health; control of blood, blood products, tissue and gametes in humans; and regulations and miscellaneous provisions. It is, potentially, a very consequential Act. To understand what needs to be different for this Act to succeed where prior national policies mostly under-achieved, it is worth examining the context and some key drivers of Nigeria’s health.